The Training Measurement Book : Best Practices, Proven Methodologies, and Practical Approaches - Bersin, Josh, 1956- (San Francisco : Pfeiffer, 2008)
The Training Measurement Book offers managers, executives, and training and human resource professionals a method for measuring their investments in a way that provides information that is both actionable, credible, and meaningful to corporate leaders. Using the methods outlined in this important resource, you can free yourself from traditional, often cumbersome measurement models and put in place pragmatic, useful, and easy-to-implement approaches for measuring training activities
Introduction. The Challenge of Training Measurement. Need for New Measurement Models. Structure of This Book. Methodology for This Research. A Personal Comment -- Chapter 1. General Principles of Training Measurement.1. Measurement Should Deliver Actionable Information.2. A Measurement Program Should Not Be Designed to Cost-Justify Training.3. Measure Training as a Support Function.4. A Measurement Program Must Meet the Needs of Multiple Audiences.5. Measurement Should Be a Process, Not a Project.6. The LMS Is a Foundation for Measurement.7. Dedicate Resources.8. Start Simply and Evolve Over Time -- Chapter 2: The Pros and Cons of Using ROI. ROI Analysis Assumes That Training Is Treated as an Investment. In-Depth ROI Measurements Are Often Difficult to Believe. In Concept, the ROI of Training Should Be Extraordinarily High. It is Very Difficult to Correlate Outcomes Specifically to Training. How Do You Make ROI Actionable?Use of "Potential ROI" During Performance Consulting."Performance-Driven" Versus "Talent-Driven" Training. Don't Let ROI Become "Return on Insecurity" -- Chapter 3: Limitations of the Kirkpatrick Model. The Kirkpatrick Levels Are Not a Complete Model. The Model Incorrectly Positions the Levels as a Hierarchy. The Kirkpatrick Model Ignores the Role of Training as a Service-Delivery Function. Kirkpatrick Misses Other Operational Measures. One Alternative: The Six-Sigma Approach to Measurement. Another Alternative: The Success Case Method(t) -- Chapter 4. The Impact Measurement Framework(r). The Business Impact Model(r). The Impact Measurement Framework(r). Summary of the Framework. Program Versus Organizational Measures. How to Use the Measurement Framework. Summary of the Measurement Models -- Chapter 5. Implementation: The Seven-Step Training Measurement Process. The Seven-Step Program Measurement Process. Best Practices in Implementation. How to Start -- Chapter 6. Measurement of Business Impact. Simplifying the Problem. Use Line-of-Business-Specific Measures. Integrate with Performance Management Processes -- Chapter 7. Measurement of Alignment. Caterpillar's Planning and Budgeting Process. CNA Insurance Training Investment Model. How Do You Measure Alignment? -- Chapter 8. Attainment: Measurement of Customer Satisfaction. The Six Sigma Approach. How Do You Operationalize the Measurement of Customer Satisfaction? -- Chapter 9. Measurement Tools and Technologies. The Role of the LMS. Training Analytics and Advanced Reporting. The KnowledgeAdvisors Solution. CLO Dashboard by Zeroed-In Technologies - Chapter 10. The Journey Forward: Focus on What Matters -- Appendix I. Case Study A: Randstad Measures Onboarding. Randstad Overview. The Business Problem. The Solution. Results. Lessons Learned. Next Steps -- Appendix II. Case Study B: Hp Develops An Integrated Measurement Process. HP Measurement Goals. HP Systematic Approach. Designed to Deliver Actionable Information. HP Solution: Standard Evaluation and Indicators. Lessons Learned -- Appendix III. Research: The State Of Training Measurement Today. What Do Training Organizations Consider Important? What Do Training Organizations Actually Measure? Budgets for Training Measurement. The Importance of a Business Plan. How Do Organizations Measure Alignment? The Role of Performance Consulting. Satisfaction with LMS Systems. Is Enough Being Spent on Training Measurement? Demographics from the Survey -- Appendix IV. Examples of Learning Measurements. Caterpillar University ROI Analyses. DAU: Business-Focused Approach. Cisco Sales Training. Microsoft Learning. Sprint University -- Appendix V. Specific Learning Measures -- Appendix VI. Training Analytics Specifications
Series from jacket
"An essential knowledge resource"--Jacket
"Featuring "The impact measurement framework" : a business-driven approach to the measurement of corporate learning."
Includes bibliographical references and index
Keywords: Training of Employees -- Human Resource Management -- Evaluation; Employees -- Training of -- Evaluation -- Case studies; Organizational learning Case Studies; Organizational learning -- Case studies